2019
DOI: 10.3390/su11226258
|View full text |Cite
|
Sign up to set email alerts
|

Road Landscape Morphology of Valley City Blocks under the Concept of “Open Block”—Taking Lanzhou City as an Example

Abstract: The unique valley geographical environment and the congestion-prone road landscape make valley city traffic jammed easily. In this paper, under the background of “open blocks”, two open patterns, which correspond to two different road landscapes ("ideal grid opening" and "open under realistic conditions"), are proposed. Taking Lanzhou city as an example, six basic statistical characteristics are used to compare and analyze the changes of road network topology in blocks to find out which open pattern is more su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…These homogeneous units also follow the earlier hypothesis whereby buildings within the units/neighbourhoods manifest the built-up morphology. Using linear features as blocks to homogenize land parcels has been done earlier (Zeng et al 2019;Kuffer et al 2020) and thus, allow generating a sort of administrative units.…”
Section: Built-up Area Homogenisationmentioning
confidence: 99%
“…These homogeneous units also follow the earlier hypothesis whereby buildings within the units/neighbourhoods manifest the built-up morphology. Using linear features as blocks to homogenize land parcels has been done earlier (Zeng et al 2019;Kuffer et al 2020) and thus, allow generating a sort of administrative units.…”
Section: Built-up Area Homogenisationmentioning
confidence: 99%
“…Dong et al proposed that after opening the closed blocks, the density of the road network will be improved and the road area can increase, a result of which the road traffic capacity is naturally improved [23]. Zeng et al proposed that open blocks have a significant effect on the improvement of network performance and capacity and found that breaking "large blocks" and developing small-scale blocks can help to alleviate traffic pressure [24]. Zhang et al studied the specific impact of different block sizes on urban traffic and analyzed the variation in generalized travel costs of transportation modes with block sizes [25].…”
Section: A Literature Reviewmentioning
confidence: 99%
“…The structure of built-up areas, including buildings, asphalt, and concrete, are inherently associated with its classes, such as residential, commercial, industrial, and transportation spaces (Chen et al, 2022; Li et al, 2022; Yin et al, 2011). The road network can be compared to the veins and arteries of a city's infrastructure, serving as vital connectors between different locations and playing a critical role in driving urban expansion (Nsikak, 2021; Zeng et al, 2019; Friedricha, 2017). With an increasing number of migrants into towns and cities, they expand, with new areas developing, leading to progressive transformation of urban structures and land use.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Shi et al (2019), road network expansion and economic activities heightened by an increase in population are major factors influencing rapid urban growth in developing countries, creating a high demand for urban land use. In furtherance, urban locations with such comparative advantages are in areas where different transportation routes converge with a high degree of compactness, connectivity, density, length, and accessibility exhibited within intra- and inter-urban road networks (Wu et al, 2020; Zeng et al, 2019; Sreelekha et al, 2016). Thus, urban road networks interact with the locations for different urban land-use activities (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%